1983
DOI: 10.1139/f83-183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia and Surface Access on Growth, Mortality, and Behavior of Juvenile Guppies, Poecilia reticulata

Abstract: Juvenile guppies (Poecilia reticulata) were fed ad libitum and maintained for 11 d at oxygen concentrations ranging from 0.5 to 8 mg/L (25–26 °C). With access to the surface, guppies showed high growth rates and low mortality at all concentrations. Without surface access, they exhibited a progressive reduction in growth rate below 2–3 mg/L and did not survive below 1 mg/L. Activity was influenced by oxygen concentration and surface access. Feeding rates declined sharply with oxygen concentration for fish witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 0 publications
1
44
1
Order By: Relevance
“…The decrease in the number of movements during exposure to hypoxia is probably a strategy for saving energy during extended exposure to hypoxia (Nilsson et al, 1993). By contrast, other studies have reported an increase in activity with moderate hypoxia exposure in adult sand goby Pomatoschistus minutus (Petersen and Petersen, 1990), adult brook trout Salvelinus fontinalis (Tang and Boisclair, 1995), and juvenile guppies Poecilia reticulata (Weber and Kramer, 1983). These responses are likely escape responses in fish that often encounter localized hypoxic zones (Petersen and Petersen, 1990).…”
Section: Series Iii: Oxygen Gradient With Changes In Flow Ratementioning
confidence: 81%
“…The decrease in the number of movements during exposure to hypoxia is probably a strategy for saving energy during extended exposure to hypoxia (Nilsson et al, 1993). By contrast, other studies have reported an increase in activity with moderate hypoxia exposure in adult sand goby Pomatoschistus minutus (Petersen and Petersen, 1990), adult brook trout Salvelinus fontinalis (Tang and Boisclair, 1995), and juvenile guppies Poecilia reticulata (Weber and Kramer, 1983). These responses are likely escape responses in fish that often encounter localized hypoxic zones (Petersen and Petersen, 1990).…”
Section: Series Iii: Oxygen Gradient With Changes In Flow Ratementioning
confidence: 81%
“…The role of fish surfacing behaviour is to access the more oxygen-rich surface layer to reduce the negative effects of hypoxia (Kramer 1987). Access to the water surface has been shown to reduce mortality in guppy (Poecilia reticulata; Weber & Kramer 1983) and reduce the negative effects on growth rate in mummichog (Fundulus heteroclitus; Stierhoff et al 2003) owing to hypoxia exposure. Therefore, denying inanga access to the surface water was the most likely cause of difference between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sloman et al (2008) reported that juvenile sculpins (Oligocottus maculosus) performed ASR, and this occurred at lower O 2 tensions compared with adults; and in juvenile guppies (Poecilia reticulata), ASR behaviour increased growth rate during hypoxia (Weber and Kramer, 1983). But the progression in ASR throughout early life in fish has not previously been correlated with events of respiratory development within the same species.…”
Section: Development Of Asrmentioning
confidence: 99%